The Analysis of Macroeconomic Factors in The Sharia Stock Index Performance: Comparison Between Indonesia and Malaysia - Sholikah, Mar'atus; Safitri, Anni (Jurnal Iqtisaduna, 2024)
This study aims to determine the effect of macroeconomic factors on the performance of the Sharia stock index in Indonesia and Malaysia during 2013-2018. The data source for this study is secondary. The data was collected using documentation and analysed using several linear regressions with the EVIEWS 8 program. The results of this study are that the exchange rate does not affect the performance of the Sharia stock index in Indonesia. In contrast, the exchange rate harms the performance of the Sharia stock index in Malaysia, meaning that the negative effect is supported when the currency depreciates, so that it will increase exports carried out by exporting companies. Inflation does not affect the performance of the Sharia stock index in Indonesia. However, in Malaysia, inflation positively affects the performance of the Sharia stock index, meaning that increasing inflation will increase the stock price index. Interest rates and production indexes do not affect the performance of the Sharia stock index in Indonesia and Malaysia.